The role of seagrass meadows in nitrogen cycling and coastal water purification - Azizova, Feruza; Mirzaev, Sayibdjan; H. Fallah, Mohammed; S, Sudarsanan; Djabbarov, Ikrom; Dewangan, Hemlata (International Journal of Aquatic Research and Environmental Studies, 2025)
Seagrass meadows serve critical roles in the coastal ecosystem by providing ecosystem services such as nitrogen cycling and water filtration. On top of this, these ‘underwater grasslands’ help mitigate problems associated with excess nitrogen surpluses in coastalwaters such as eutrophication and harmful algal blooms. This paper analyzes the impacts of seagrasses on the nitrogen cycle, including nitrogen uptake, assimilation, denitrification, and sediment stabilization. In addition, this paper discusses the role of seagrasses in the prevention of eutrophication and their improvements towards water quality as well as their overall ecosystem service value. Understanding these processes is essential for the sustainable conservation of coastal ecosystems and water qualitymanagement.
Keywords: Seagrass; Meadows; Coastal ecosystems; Nitrogen; Denitrification, and Eutrophication